Increasing reliability of traction electric motors of diesel locomotives taking into account thermophysical parameters of insulation and armature winding conductors - V. I. Kiselev; T. O. Vakhromeeva; A. I. Fedyanin (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. The issue of ensuring the operable state of the DC traction motor is relevant due to its large-scale use on diesel locomotives, including modern powerful motors, operating on lines with increased train masses. At present, a rather difficult situation has developed in the locomotive industry with the failure of diesel locomotive traction electric motors due to a decrease in the insulation resistance of the armature windings of the electric motors and their subsequent breakdowns: up to 28 % of the total number of failures of electric motors are due to breakdown of the hull insulation and interturn short circuit of the armature and 13 % of cases are due to reduction in the resistance of the insulating material.Materials and methods. The paper considers the main directions of scientific research on the causes of insulation integrity failure, which lead to unscheduled repairs of traction motors. The theoretical substantiation of the root causes of insulation destruction is based on the importance of taking into account the coefficients of thermal linear expansion of copper and its insulating materials. In order to study thermodynamic processes in the winding of a traction motor, a computational finite element model of a winding coil laid in the groove of the armature core has been developed. The winding model is represented separately by a conductor and insulation, between which contact conditions are specified. The conductor of the calculation model heats up to 120 °C from the current flow. Mathematical apparatus embedded in the MSC calculation program, Patran – Nastran, made it possible to evaluate the deformation of the conductor relative to the insulation as a result of a linear increment due to thermal expansion.Results. With the help of mathematical modelling and based on the results of finite element analysis, the confirmation of the theoretical justification is clearly shown. The difference in elongation during heating of the motor armature conductor and insulation, obtained by mathematical modelling, is 0.6 mm and is significant for the winding (consisting of a conductor and insulation), which is usually considered as a single whole body.Discussion and conclusion. The obtained result shows the need for more detailed studies to select the technology for the insulation of the DC traction motor. The use of insulating materials for the armature winding with coefficients of thermal linear expansion equal to the coefficient of thermal expansion of the copper conductors of the winding will improve the reliability of traction electric motors of diesel locomotives in operation.